A study of growth, development and N-fixation of several white clover (Trifolium repens L.) cultivars under different water deficit and phosphorus levels : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Wang, Xinjun (Massey University, 1991)
White clover (Trifolium repens L.) is one of the most important pasture plants in New Zealand. It contributes nitrogen, high quality forage and seasonal spread of production. However, it has high requirements for phosphate and does not persist well under moisture stress condition.s In this study the effects of water deficit level and phosphorus (P) level on the growth, development and N-fixation of different white clover cultivars have been studied. Several New Zealand and overseas white clover cultivars of contrasting morphological characteristics were selected for this study. These cultivars were Kopu, Pitau, Dusi, Haifa, Huia, Tahora and Whatawhata. The main objectives of this study were to determine the effects of water stress and phosphorus levels on growth, development, and N-fixation of these cultivars and to identify the plant characteristics most effective in distinguishing the cultivars used in the study. The research approach was to measure the responses of these cultivars to water deficit and P fertility treatments; and the responses were then related to selected plant characteristics, particularly morphological characteristics. Attempt was also made to distingish the cultivars using multivariate analysis techniques. The results of this study showed that the cultivars had responded differently to water deficit treatment and P treatment. The retardation they suffered in their growth and development, expressed by both dry weight (DW) and growth rate of stonon components (leaf, petiole and branch), was significantly different and, in many cases, could be related back to their morphology and development characteristics. Cultivars of small stature, such as Whatawhata and Tahora, were generally less affected by the stress treatments. Cultivars grown well under control conditions, such as Kopu and Haifa, suffered more severely under stress conditions. For all cultivars, parameters association with leaf area were more sensitive to water deficit stress than those associated with growing points. The study of plant water status of these cultivars under progressively decreasing water availability failed to identify any significant difference between the cultivars in their ability to avoid dehydration at medium to high water deficity stress levels. So it could be suggested that the diference between the cultivars represented their ability to tolerate water stress and was unlikely to be associated with their dehydration avoidance ability but more likely to be associated with morphological characteristics such as deep root and reducing leaf area when water deficit stress occurred. The cultivats were different in their N-fixation ability, as measured by the acetylene reduction analysis (ARA), and this difference was related strongly to leaf size. But when expressed as ARA per unit DW, the difference between the cultivars was non-significant. Overall, under control conditions, mainly the morphological characteristics, such as leaf size, leaf weight and petiole length, caused the difference between cultivars, other characteristics, such as the plant DW components, DW partitioning, and P and N partitioning in plant components, were less important. Among the morphological characteristics, leaf size and leaf weight per stolon were the most important characteristics differentiating between cultivars. These two characteristcs were also the most important for determining plant yield. Under water deficit stress and P deficiency treatment, root DW and branch number were the two most important characteristics differentiating between the cultivars. ABSTRACT White clover (Trifolium repens L.) is one of the most important pasture plants in New Zealand. It contributes nitrogen, high quality forage and seasonal spread of production. However, it has high requirements for phosphate and does not persist well under moisture stress conditions. In this study the effects of water deficit level and phosphorus (P) level on the growth, development and N-fixation of different white clover cultivars have been studied. Several New Zealand and overseas white clover cultivars of contrasting morphological characteristics were selected for this study. These cultivars were Kopu, Pitau, Dusi, Haifa, Huia, Tahora and Whatawhata. The main objectives of this study were to determine the effects of water stress and phosphorus levels on growth, development, and N-fixation of these cultivars and to identify the plant characteristics most effective in distinguishing the cultivars used in the study. The research approach was to measure the responses of these cultivars to water deficit and P fertility treatments; and the responses were then related to selected plant characteristics, particularly morphological characteristics. Attempt was also made to distinguish the cultivars using multivariate analysis techniques. The results of this study showed that the cultivars had responded differently to water deficit treatment and P treatments. The retardation they suffered in their growth and development, expressed by both dry weight (DW) and growth rate of stolon components (leaf, petiole and branch), was significantly different and, in many cases, could be related back to their morphology and development characteristics. Cultivars of small stature, such as Whatawhata and Tahora, were generally less affected by the stress treatments. Cultivars grown well under control conditions, such as Kopu and Haifa, suffered more severely under stress conditions. For all cultivars, parameters associated with leaf area were more sensitive to water deficit stress than those associated with growing points. The study of plant water status of these cultivars under progressively decreasing water availability failed to identify any significant difference between the cultivars in their ability to avoid dehydration at medium to high water deficit stress levels. So it could be suggested that the difference between the cultivars represented their ability to tolerate water stress and was unlikely to be associated with their dehydration avoidance ability but
Keywords: White clover; Plant-water relationships; Effect of phosphorus on plants; Effect of water levels on plants